Challenging the political narrative a comparative analysis of the political fact-checking practices in Philippine newsrooms - Adolfo, Regina Marie Padero; Cuyco Ma. Jan Felicia Dacanay
Fact-checking initiatives in the Philippines intensified in response to the spate of political mis- and disinformation that persisted even after the May 2022 elections. where the son of late dictator Ferdinand Marcos Jr. won the presidency by a landslide. As Philippine news media continue to receive accusations of bias and peddling 'fake news", this study looks at the various ways in which Filipino professional fact checkers adhere to accepted fact checking standards and practices in covering political claims. Drawing theoretical insights from Ceron and Carrara's Reputational Theory of Political Falsehoods (2021) and Graves' Anatomy of a Fact Check (2017), this study content analyzed fact checks and published statements from eight Philippine news outlets, as classified into five categories: International Fact Checking Network signatories, Philippine Fact-Checker Incubator (PFCI) mentees, non-PFCI mentees, regional news media and alternative news media. Fact checkers were also interviewed to identify the individual and organizational factors influencing certain political fact-checking routines. Findings reveal that some professional fact checkers have adapted their approach to selecting which claims to verify, while still upholding core journalistic principles of accuracy and transparency in other areas of fact-checking practice. The study highlights the gaps, in the fact-checking strategies of different news outlets and suggests ways moving forward for the local fact-checking scene.